Improvement of Vocal Pathologies Diagnosis Using High-Speed Videolaryngoscopy - Tsuji,Domingos Hiroshi (2014)
Introduction  The study of the dynamic properties of vocal fold vibration is important for understanding the vocal production mechanism and the impact of organic and functional changes. The advent of high-speed videolaryngoscopy (HSV) has provided the possibility of seeing the real cycle of vocal fold vibration in detail through high sampling rate of successive frames and adequate spatial resolution. Objective  To describe the technique, advantages, and limitations of using HSV and digital videokymography in the diagnosis of vocal pathologies. Methods  We used HSV and digital videokymography to evaluate one normophonic individual and four patients with vocal fold pathologies (nodules, unilateral paralysis of the left vocal fold, intracordal cyst, and adductor spasmodic dysphonia). The vocal fold vibration parameters (glottic closure, vibrational symmetry, periodicity, mucosal wave, amplitude, and glottal cycle phases) were assessed. Results  Differences in the vocal vibration parameters were observed and correlated with the pathophysiology. Conclusion  HSV is the latest diagnostic tool in visual examination of vocal behavior and has considerable potential to refine our knowledge regarding the vocal fold vibration and voice production, as well as regarding the impact of pathologic conditions have on the mechanism of phonation.